2008
DOI: 10.1242/jcs.026989
|View full text |Cite
|
Sign up to set email alerts
|

Replication-timing-correlated spatial chromatin arrangements in cancer and in primate interphase nuclei

Abstract: Summary Using published high-resolution data on S-phase replication timing, we determined the three-dimensional (3D) nuclear arrangement of 33 very-early-replicating and 31 very-late-replicating loci. We analyzed diploid human, non-human primate and rearranged tumor cells by 3D fluorescence in situ hybridization with the aim of investigating the impact of chromosomal structural changes on the nuclear organization of these loci. Overall, their topology was found to be largely conserved between cell types, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 60 publications
7
42
1
2
Order By: Relevance
“…[33][34][35] The strongest functional evidence linking chromosome architecture and cellular function was recently demonstrated in rod cell nuclei. 36 The authors convincingly demonstrated regular and inverted chromosomal architecture in rod cells, and this architecture was associated with diurnal and nocturnal vision.…”
Section: Disruption Of Nuclear Architecture In Hodgkin's Lymphomamentioning
confidence: 99%
“…[33][34][35] The strongest functional evidence linking chromosome architecture and cellular function was recently demonstrated in rod cell nuclei. 36 The authors convincingly demonstrated regular and inverted chromosomal architecture in rod cells, and this architecture was associated with diurnal and nocturnal vision.…”
Section: Disruption Of Nuclear Architecture In Hodgkin's Lymphomamentioning
confidence: 99%
“…Furthermore, non-random positioning in interphase nuclei is known to be of importance for genomic stability and formation of chromosome aberrations. Tissue specificity of chromosomal translocations could be due to tissue specific genome organization [5][6], and a positive correlation between spatial proximity of chromosomes/ genes in interphase nuclei and translocation frequencies was shown [5][6][7][8][9][10]. Three-dimensional (3D) fluorescence in situ hybridization (FISH) analysis became a major tool 3D-positioning of chromosomes 8 and 21 in AML for studying this higher order chromatin organization in the cell nucleus [4; 11-15].…”
Section: Introductionmentioning
confidence: 99%
“…Many lines of evidence suggest the functional significance of genome architecture, including the existence of chromosomes territories [1], the correlation between radial positioning of chromosomes with gene density, transcriptional activity, replication timing and chromosome size [2][3][4][5], the tissue-specific spatial configurations of chromosomes relative to one another [6,7], the co-localization of disparate DNA elements into functionally defined aggregates or "factories" [9][10][11][12][13], and the predisposition to human disease, including cancer by predisposition to acquisition of karyotypic defects [14][15][16][17]. Collectively, these various lines of evidence indicate an intimate relationship between genome structure and function.…”
Section: Introductionmentioning
confidence: 99%